Analisis Semiotika Charles Sanders Peirce Tentang Makna Logo Pariwisata Kabupaten Sukabumi - Abdul Malik; Bachrul Restu Bagja; Raray Istianah (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2021)
This study aims to examine the symbols contained in the tourism logo of Sukabumi GURILAPSS Regency owned by the Tourism Office of Sukabumi Regency, know the meaning of the symbols of the tourism logo of Sukabumi GURILAPSS Regency, and know the link of meaning contained in the tourism logo of Sukabumi GURILAPSS Regency. This study used qualitative research using the semiotic analysis of Charles Sanders Peirce. The focus of the study is the symbols contained in the Tourism logo based on the semiotic triangle meaning theory with three universal categories such as Firstness, Secondness, and Thirdness. The results of this study showed the tourism logo of Sukabumi GURILAPSS regency has three symbols, namely turtle logogram, GURILAPSS Logotype, and Logotype tagline pesona sukabumi. The symbol of turtle logogram has the meaning of turtle as an animal that is preserved in Sukabumi Regency. Turtles are also a surviving fauna in sukabumi district. Logotype GURILAPSS stands for several words namely Mountain, Jungle, Sea, Beach, River, and Cultural Arts, and Logotype tagline 'Pesona Sukabumi' is a tourism tagline of sukabumi regency, it can be concluded that the symbol logogram turtle has meaning as an icon of sukabumi regency, logotype GURILAPSS and logotype tagline as tourism culture sukabumi.